Bidimensional Exploration of the warm-Temperature Ionised gaS (BETIS) I. Showcase sample and first results - Gonzalez-Diaz, R.; Rosales-Ortega, F. F.; Galbany, L.; Anderson, J. P.; Jimenez-Palau, C.; Kopsacheili, M.; Kuncarayakti, H.; Lyman, J. D.; Sanchez, S. F. (EDP Sciences, 2025)
We present the Bidimensional Exploration of the warm-Temperature Ionised gaS (BETIS) project, designed for the spatial and spectral study of the diffuse ionised gas (DIG) in a selection of nearby spiral galaxies observed with the MUSE integral-field spectrograph. Our primary objective is to investigate the various ionisation mechanisms at play within the DIG. We analysed the distribution of high- and low-ionisation species in the optical spectra of the sample on a spatially resolved basis. We introduced a new methodology for spectroscopically defining the DIG, optimised for galaxies of different resolutions. Firstly, we employed an innovative adaptive binning technique on the observed datacube based on the spectroscopic signal-to-noise ratio (S/N) of the collisional [S II] line to increase the S/N of the rest of the lines including [O III], [O I], and He I. Subsequently, we created a DIG mask by eliminating the emissions associated with both bright and faint H II regions. We also examined the suitability of using H alpha equivalent width (EWH alpha) as a proxy for defining the DIG and its associated ionisation regime. Notably, for EWH alpha < 3 & Aring; - the expected emission from hot low-mass evolved stars (HOLMES) - the measured value is contingent on the chosen population synthesis technique performed. Our analysis of the showcase sample reveals a consistent cumulative DIG fraction across all galaxies in the sample, averaging around 40%-70%. The average radial distribution of the [N II]/H alpha, [S II]/H alpha, [O I]/H alpha, and [O III]/H beta ratios are enhanced in the DIG regimes (up to 0.2 dex). It follows similar trends between the DIG regime and the H II regions, as well as the H alpha surface brightness (Sigma(H alpha)), indicating a correlation between the ionisation of these species in both the DIG and the H II regions. The DIG loci in typical diagnostic diagrams are found, in general, within the line ratios that correspond to photoionisation due to the star formation. There is a noticeable offset correspondent to ionisation due to fast shocks. However, an individual diagnosis performed for each galaxy reveals that all the DIG in these galaxies can be attributed to photoionisation from star formation. The offset is primarily due to the contribution of Seyfert galaxies in our sample, which is closely aligned with models of ionisation from fast shocks and galactic outflows, thus mimicking the DIG emission. Our results indicate that galaxies exhibiting active galactic nucleus (AGN) activity should be considered separately when conducting a general analysis of the DIG ionisation mechanisms, since this emission is indistinguishable from high-excitation DIG.